Effect of feeding a protein supplement during the latter part of the grazing season to two-year-old steers on bluestem pasture. - Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
The nutritive value of bluestem pasture usually beings to decline rapidly after mid-summer. This test is concerned with what effect the feeding of a protein supplement after mid-summer will have on cattle gains and conditions. It is hoped that by starting the feeding at different times the most opportune time to start feeding may be determined.
Keywords: Beef; Protein; Bluestem pasture; Gain